Low-Grade Central Fibroblastic Osteosarcoma in an Unusual Location: A Case Report. (21st September 2018) - Khafateh, Youssef; Kouba, Lamia; Jordan, Adrienne; Alatassi, Houda
Abstract: Osteosarcoma is the most common nonhematological malignant primary bone tumor. Low-grade central osteosarcoma, also known as intraosseous well-differentiated osteosarcoma, is a rare variant of osteosarcoma that arises from the medullary cavity of bone. It accounts for only 1% to 2% of all osteosarcomas and has an equal sex distribution. The peak incidence is in the second and third decades of life. We report a case of 33-year-old male who presented at our institution with a palpable nontender left chest wall mass that was noticed few months ago. CT scan of the chest revealed a large sclerotic mass within the left lateral seventh rib, associated with aggressive periosteal reaction and sunburst pattern, highly suspicious for a primary osteosarcoma. Biopsy was obtained from the mass and demonstrated long sweeping fascicles of moderately atypical fibroblastic cells surrounding streamers of woven bone. These morphologic findings are consistent with low-grade central fibroblastic osteosarcoma, despite occurring in a rare location. Microscopic examination of the resection specimen confirmed the diagnosis and showed the lesion extended through the rib into surrounding soft tissues. Approximately 80% of low-grade central osteosarcomas are located in the long bones with a distinct predilection for the distal femur and proximal tibia. The diagnosis remains challenging due to the relatively nonspecific radiological and histological findings. The treatment of low-grade central osteosarcoma is primarily surgical, but if the diagnosis is not made in an accurate and timely fashion, then the prognosis is significantly worse with high chance of recurrence of higher-grade disease.